Análisis del impacto de ruido de fondo y tiempo de reverberación en procesos cognitivos por medio de Auralizaciones (2017)
The research below proposes a method to analyze the influence of reverberation time and background noise upon cognitive processes of attention, memory and executive function. To characterize the acoustic variable (reverberation time) acoustic models are implemented using the software CATT-Acoustic, making auralizations with the messages with four different reverberation time conditions, matching a characteristic enclosure of a learning area from the San Buenaventura University, to use along with the psychological tools. Background noise conditions from the room were measured with a binaural head [Cortex MK2b, 01dB], assessing four of this levels. The pilot test mode applied showed a negligible impact from the acoustic variable on cognitive processes, due to the amount of specimens and variations observed on the application protocol, i.e. examination mode, timekeeping of the test, compromising consequently the results. In a complementary test in which the amount of four specimen groups where increased it showed a positive influence of a high background noise in four components of the verbal memory plot curve, where the attention and memory processes are assessed, and a negative influence of a long reverberation time, in the verbal memory components as well as in the Wechsler memory scale.